The Uses of Digital Technologies in Schools. A Bourdieusian Analysis of Upper-Secondary School Teachers and Students in Rome - Parziale, Fiorenzo; Cavagnuolo, Michela; Matrella, Alfredo (Italian Sociological Review, 2024)
Drawing on Bourdieu’s (1979, 1984) habitus theory, this paper analyses the complex relationship between the use of digital technologies in schools and the reproduction of educational inequalities, through research based on two online surveys administered to students and teachers of 20 upper-secondary schools in Rome. Among the main findings of the research is the “complicity” between the habitus and cultural capital of individual agents and the way in which the educational field reproduces organisational principles of social division of labour. In particular, alongside the persistent lack of familiarity with digital technologies seen in women, even among teachers, the results of the surveys pointed towards the tendency of students from middle-class backgrounds and schools to employ a more critical use of digital technologies in class, compared to those of the working-class. However, it is important to note that a number of teachers in vocational institutions, some of whom from a working-class background, are inclined towards a more selective and equally critical use of technologies. The presence of this minority of teachers could partly mitigate the reproduction of educational inequalities due to social origin.